Complaints after intestinal infections in young children in the 6 mo long catamnesis and looking for their pathogenetic mechanisms - Bylikh, V. M.; Білих, В. М. (НУОЗ ім. П. Л. Шупика, 2022)
The aim. Evaluate parents' complaints of their children's intestinal health during the first 6 months after bacterial enterocolitis or rotavirus gastroenteritis by direct interview and comparison of the resulting follow-up with the coprological indicators at the peak of the infectious process.
ORCID: 0000-0002-9873-2028